Furnace tests on unprotected and protected concrete filled structural hollow sections. (November 2015) - Rush, David; Bisby, Luke; Gillie, Martin; Jowsey, Allan; Lane, Barbara
Abstract: The accurate prediction of cross-sectional temperatures within concrete filled steel hollow (CFS) sections is critical for the accurate prediction of fire resistance. Whilst there have been many thermal and structural tests conducted on CFS columns, there are few that report the full cross-sectional thermal profile, and when they are reported, the sensor density is low, hindering the ability to validate models. This paper presents furnace tests and thermal modelling on 14 unprotected and 20 protected CFS sections, and examines the effect of several parameters on cross-sectional thermal profiles, as well as assessing the accuracy of both Eurocode thermal analysis guidance and intumescent fire protection design guidance. This paper shows that; (a) the assumptions within the Eurocode guidance can lead to large over-estimations in cross-sectional temperatures; (b) proposes new thermal modelling assumptions in three key areas; and (c) shows that the current intumescent fire protection design guidance is very conservative. Highlights: Thermal tests on unprotected and protected concrete filled hollow (CFS) sections. Timing of interface gap formation based on section size inferred from test data. Improved thermal modelling approach for cross-sectional temperatures is given. Tests show current guidance for intumescent protection systems to be conservative. Design recommendations are given for unprotected and protected CFS sections.